Bamboo-like stainless steel guardrail production and processing technology

By applying imitation bamboo paint and protective coating on the stainless steel guardrail and performing photocuring treatment, the problem of the coating prone to aging and falling off in the existing imitation bamboo process is solved, and the super-hydrophobic, antibacterial, ultraviolet and corrosion-resistant properties of imitation bamboo stainless steel guardrail are achieved, extending the service life.

CN119529659AActive Publication Date: 2025-02-28JIANGXI HANGXI METAL PROD CO LTD

Patent Information

Application Number
CN202411789617.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing imitation bamboo process coats imitation bamboo paint on metal materials, which causes the coating to age and fall off, resulting in accelerated rust of metal materials.

Method used

A bamboo-imitation stainless steel guardrail production and processing technology is adopted. By assembling, welding and forming stainless steel pipes, and frosting, polishing, washing and drying, then applying bamboo paint and protective coatings to form bamboo paint and protective layers, and the adhesion and durability of the coating are enhanced by light curing treatment.

Benefits of technology

The prepared bamboo stainless steel guardrail has super hydrophobic, antibacterial, ultraviolet and corrosion resistance, thereby greatly extending its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of stainless steel, in particular to a bamboo-like stainless steel guardrail production and processing technology which comprises the steps that a formed stainless steel guardrail is treated in a spraying mode, and a bamboo paint layer and a protective layer are sequentially constructed on the surface of the stainless steel guardrail by optimizing protective paint; composite zinc-titanium hydrotalcite and double-bond nano silicon dioxide are introduced into the protective coating to serve as filler, anhydrous zinc acetate, titanium tetrachloride and dopamine hydrochloride serve as raw materials, and polydopamine-coated zinc-titanium hydrotalcite is prepared through a hydrothermal method. Then depositing an antibacterial hydrophobic copolymer synthesized by taking 3-methacryloyl dopamine, styrene, dodecafluoroheptyl methacrylate, dimethylaminoethyl methacrylate and citronellyl methyl methacrylate as raw materials; the waterborne polyurethane emulsion is used as a photocurable protective coating base material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of stainless steel, in particular to a production and processing technology of a bamboo-like stainless steel guardrail. Background Art

[0002] In the existing architectural design of gardens and parks, bamboo is a common and poetic decorative element. However, in actual application, there are many difficulties in planting and transplanting real bamboo, which will affect the overall quality and viewing effect of the architectural design.

[0003] In order to avoid difficulties such as transplanting live bamboo, imitation bamboo technology has entered the market. Most of them are made by coating imitation bamboo paint on metal materials. There are also problems such as easy aging and falling off of the coating, which in turn accelerates the rust of the metal material. Summary of the invention

[0004] The purpose of the invention is to provide a production and processing technology of imitation bamboo stainless steel guardrail to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A production and processing technology of imitation bamboo stainless steel guardrail, comprising the following steps: S1: Assemble and weld the stainless steel pipes to obtain the stainless steel guardrail, and then perform grinding, polishing, washing and drying to obtain the pre-treated stainless steel guardrail; S2: applying the imitation bamboo paint on the surface of the pretreated stainless steel guardrail, drying it, and forming a bamboo paint layer; S3: mixing the waterborne polyurethane emulsion, the composite zinc-titanium hydrotalcite and the double-bonded nano-silica, adding a photoinitiator, and ultrasonically stirring to obtain a protective coating; S4: coating the protective coating on the surface of the bamboo paint layer, performing light curing treatment, forming a protective layer, and obtaining a bamboo-like stainless steel guardrail.

[0006] Furthermore, the protective coating comprises, by weight, 31-57 parts of aqueous polyurethane emulsion, 1-2 parts of photoinitiator, 2-6 parts of composite zinc-titanium hydrotalcite, and 1-3 parts of double-bonded nano-silicon dioxide.

[0007] Furthermore, the mass ratio of the composite zinc-titanium hydrotalcite and the double-bonded nano-silica is 2:1.

[0008] Furthermore, the working conditions of the light curing treatment are: irradiation under 365nm ultraviolet light for 5-10min.

[0009] Furthermore, the preparation of double-bonded nano-silica includes the following steps: mixing nano-silica and isopropanol, adding a mixed solution of vinyltrimethoxysilane, deionized water and anhydrous ethanol, keeping warm at 70-80°C for 4-5h, centrifuging, washing and drying to obtain double-bonded nano-silica.

[0010] Further, the preparation of the composite zinc-titanium hydrotalcite comprises the following steps: (1) Mix zinc nitrate, ethanol and deionized water, add titanium tetrachloride, add dopamine hydrochloride and mix, adjust the pH to 8, transfer to a reactor, keep warm at 118-122°C for 22-24 hours, centrifuge, wash with ethanol and deionized water for 3-5 times, and obtain polydopamine-coated zinc-titanium hydrotalcite; (2) The polydopamine-coated zinc-titanium hydrotalcite, anhydrous ethanol and deionized water are mixed, ultrasonically stirred for 20-30 minutes, heated to 78-82°C, added with an antibacterial hydrophobic copolymer, stirred for 2-3 hours, centrifuged, washed, dried and ground to obtain a composite zinc-titanium hydrotalcite.

[0011] Further, the preparation of the aqueous polyurethane emulsion comprises the following steps: In a nitrogen atmosphere, isophorone diisocyanate, polycarbonate diol and dibutyltin dilaurate are mixed, the temperature is raised to 63-68°C in an oil bath for 2-3 hours, a mixture of 2,2-dihydroxymethylpropionic acid and acetone is added, the temperature is raised to 78-82°C and kept warm for 1-2 hours, the temperature is lowered to 68-72°C, a mixture of castor oil and acetone is added, the temperature is lowered to 58-62°C, pentaerythritol triacrylate and antibacterial hydrophobic copolymer are added, the temperature is kept warm for 2-3 hours, the temperature is lowered to 48-52°C, triethylamine is added, deionized water is added for emulsification, and rotary evaporation is performed to obtain an aqueous polyurethane emulsion with a solid content of 30-35%.

[0012] Furthermore, the mass ratio of isophorone diisocyanate, polycarbonate diol, 2,2-dihydroxymethylpropionic acid, castor oil, pentaerythritol triacrylate, and antibacterial hydrophobic copolymer is 7:10:0.8:1.5:1:1.4.

[0013] Further, the preparation of the antibacterial hydrophobic copolymer comprises the following steps: 1) Under a nitrogen atmosphere, β-citronellol, triethylamine and dichloromethane were mixed, transferred to an ice-water bath, methacryloyl chloride was added, and then kept at 18-25°C for 7-8h, filtered under reduced pressure, concentrated by rotary evaporation, extracted with ether for 3-5 times, extracted and washed with dilute hydrochloric acid and saturated sodium bicarbonate solution for 1-3 times, concentrated by rotary evaporation, and purified by silica gel column using n-hexane and ethyl acetate in a volume ratio of 9:1 as eluent to obtain citronellol methyl methacrylate; 2) Mix deionized water and sodium dodecyl sulfate, add acrylic acid, dodecafluoroheptyl methacrylate, dimethylaminoethyl methacrylate, citronellyl methyl methacrylate, and 3-methacryloyl dopamine, stir for 20-30 minutes, add a mixture of potassium persulfate and deionized water, heat to 78-82° C. and keep warm for 2-3 hours, cool, centrifuge, wash, and dry to obtain an antibacterial hydrophobic copolymer.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a production and processing technology for a bamboo-like stainless steel guardrail. By optimizing the coating composition and the processing technology, a super-hydrophobic, antibacterial, anti-ultraviolet and corrosion-resistant bamboo-like stainless steel guardrail is prepared, thereby greatly extending the service life of the bamboo-like stainless steel guardrail.

[0015] The present invention adopts a spraying method to process the formed stainless steel guardrail. By optimizing the protective coating and then performing a photocuring treatment, a bamboo paint layer and a protective layer are sequentially constructed on the surface of the stainless steel guardrail, thereby preventing the bamboo paint layer from falling off, thereby greatly improving the appearance and durability of the stainless steel guardrail.

[0016] In order to give the bamboo-like stainless steel guardrail excellent UV resistance, the present invention introduces composite zinc-titanium hydrotalcite as filler in the protective coating, uses anhydrous zinc acetate, titanium tetrachloride and dopamine hydrochloride as raw materials, and uses a hydrothermal method to prepare polydopamine-coated zinc-titanium hydrotalcite. In order to improve the uniformity of dispersion of the polydopamine-coated zinc-titanium hydrotalcite in the protective coating, dopamine in the polydopamine-coated zinc-titanium hydrotalcite is used as an anchoring agent, and 3-methacryloyl dopamine, styrene, dodecafluoroheptyl methacrylate, and dimethylaminoethyl methacrylate are deposited. The invention discloses an antibacterial hydrophobic copolymer synthesized with 2-hydroxy-1-nitro-2-nitro-1-ol and 2-hydroxy-1-nitro-2-ol as raw materials, wherein dodecafluoroheptyl methacrylate in the copolymer imparts low surface energy, and the cationic monomers dimethylaminoethyl methacrylate and 2-hydroxy-1-nitro-2-ol synergistically impart excellent antibacterial properties, wherein 2-hydroxy-1-nitro-2-ol is prepared by modifying the natural antibacterial agent citronellol through an esterification reaction; 3-methacryloyldopamine is beneficial for the copolymer to be deposited on the surface of the zinc-titanium hydrotalcite coated with polydopamine, thereby imparting the composite zinc-titanium hydrotalcite with excellent antibacterial and hydrophobic properties.

[0017] In order to improve the wear resistance of the protective layer, nano-silica is introduced as a filler in the protective coating. In order to improve the uniformity and firmness of the dispersion of nano-silica in the protective layer, vinyltrimethoxysilane is used to make it double-bonded. By controlling the mass ratio of composite zinc-titanium hydrotalcite and double-bonded nano-silica in the coating, a super-hydrophobic and wear-resistant surface of the protective layer is constructed to improve the durability of the bamboo-like stainless steel guardrail.

[0018] The present invention adopts water-based polyurethane emulsion as a base material of a photocurable protective coating, uses isophorone diisocyanate and polycarbonate diol as raw materials to prepare a prepolymer, uses dimethylol propionic acid as a hydrophilic chain extender, uses castor oil as an internal cross-linking agent, and uses pentaerythritol triacrylate and an antibacterial hydrophobic copolymer for end-capping modification, thereby greatly improving the bonding strength between the coating and the stainless steel guardrail, improving the hydrophobicity and antibacterial property of the coating, and extending the service life of the stainless steel guardrail. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.

[0021] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0022] Embodiment 1: A production and processing technology of bamboo-like stainless steel guardrail, comprising the following steps: S1: Assemble and weld the stainless steel pipes to obtain the stainless steel guardrail, and then perform grinding, polishing, washing and drying to obtain the pre-treated stainless steel guardrail; S2: applying the imitation bamboo paint on the surface of the pretreated stainless steel guardrail, drying it, and forming a bamboo paint layer; S3: mixing the waterborne polyurethane emulsion, the composite zinc-titanium hydrotalcite and the double-bonded nano-silica, adding a photoinitiator, and ultrasonically stirring to obtain a protective coating; The protective coating is composed of 31 parts of waterborne polyurethane emulsion, 1 part of photoinitiator, 2 parts of composite zinc-titanium hydrotalcite, and 1 part of double-bonded nano-silicon dioxide in parts by weight; The mass ratio of composite zinc-titanium hydrotalcite and double-bonded nano-silica is 2:1; The preparation of the double-bonded nano-silica comprises the following steps: mixing 2 g of nano-silica and 80 mL of isopropanol, adding a mixed solution of 1.2 g of vinyltrimethoxysilane, 6 mL of deionized water, and 44 mL of anhydrous ethanol, keeping warm at 70° C. for 5 h, centrifuging, washing, and drying to obtain the double-bonded nano-silica; The preparation of the composite zinc-titanium hydrotalcite comprises the following steps: (1) 3.7 g of zinc nitrate, 400 mL of ethanol, and 400 mL of deionized water were mixed, 1.1 mL of titanium tetrachloride was added, 0.4 g of dopamine hydrochloride was added and mixed, the pH was adjusted to 8, the mixture was transferred to a reactor, kept at 118 ° C for 24 h, centrifuged, and washed with ethanol and deionized water for 3 times in sequence to obtain polydopamine-coated zinc-titanium hydrotalcite; (2) 1.2 g of polydopamine-coated zinc-titanium hydrotalcite, 60 mL of anhydrous ethanol, and 60 mL of deionized water were mixed, ultrasonically stirred for 20 min, heated to 78 °C, 1.8 g of antibacterial hydrophobic copolymer was added, stirred for 2 h, centrifuged, washed, dried, and ground to obtain composite zinc-titanium hydrotalcite; The preparation of the aqueous polyurethane emulsion comprises the following steps: Under a nitrogen atmosphere, 7g of isophorone diisocyanate, 10g of polycarbonate diol, and 3 drops of dibutyltin dilaurate were heated to 63°C for 3h in an oil bath, 0.8g of 2,2-dihydroxymethylpropionic acid and a mixture of 5mL of acetone were added, the temperature was raised to 78°C and kept for 2h, the temperature was lowered to 68°C, 2.8g of castor oil and 5mL of acetone were added, the temperature was lowered to 58°C, 1g of pentaerythritol triacrylate and 1.4g of antibacterial hydrophobic copolymer were added, the temperature was kept for 2h, the temperature was lowered to 48°C, 0.8g of triethylamine was added, deionized water was added for emulsification, and a water-based polyurethane emulsion with a solid content of 33% was obtained; The preparation of the antibacterial hydrophobic copolymer comprises the following steps: 1) Under nitrogen atmosphere, 9.1 mL of β-citronellol, 8.3 mL of triethylamine, and 100 mL of dichloromethane were mixed, transferred to an ice-water bath, 5.8 mL of methacryloyl chloride was added, and then kept at 18°C ​​for 8 h, filtered under reduced pressure, concentrated by rotary evaporation, extracted with ether for 3 times, extracted and washed with dilute hydrochloric acid and saturated sodium bicarbonate solution in turn, concentrated by rotary evaporation, and purified by silica gel column using n-hexane and ethyl acetate in a volume ratio of 9:1 as eluent to obtain citronellol methyl methacrylate; 2) 20 mL of deionized water and 0.5 g of sodium dodecyl sulfate were mixed, 3 g of styrene, 4.5 g of dodecafluoroheptyl methacrylate, 1.5 g of dimethylaminoethyl methacrylate, 1.1 g of citronellyl methyl methacrylate, and 1.2 g of 3-methacryloyl dopamine were added, and the mixture was stirred for 20 min, and 0.6 g of potassium persulfate and 20 mL of deionized water were added, and the mixture was heated to 78 ° C and kept warm for 3 h, cooled, centrifuged, washed, and dried to obtain an antibacterial hydrophobic copolymer; S4: coating the protective coating on the surface of the bamboo paint layer, photocuring the coating to form a protective layer, and obtaining a bamboo-like stainless steel guardrail; the working conditions of the photocuring treatment are: irradiating the bamboo paint layer under 365nm ultraviolet light for 8 minutes.

[0023] Embodiment 2: A production and processing technology of bamboo-like stainless steel guardrail, comprising the following steps: S1: Assemble and weld the stainless steel pipes to obtain the stainless steel guardrail, and then perform grinding, polishing, washing and drying to obtain the pre-treated stainless steel guardrail; S2: applying the imitation bamboo paint on the surface of the pretreated stainless steel guardrail, drying it, and forming a bamboo paint layer; S3: mixing the waterborne polyurethane emulsion, the composite zinc-titanium hydrotalcite and the double-bonded nano-silica, adding a photoinitiator, and ultrasonically stirring to obtain a protective coating; The protective coating is composed of 43 parts of waterborne polyurethane emulsion, 1.5 parts of photoinitiator, 4 parts of composite zinc-titanium hydrotalcite, and 2 parts of double-bonded nano-silicon dioxide in parts by weight; The mass ratio of composite zinc-titanium hydrotalcite and double-bonded nano-silica is 2:1; The preparation of the double-bonded nano-silica comprises the following steps: mixing 2 g of nano-silica and 80 mL of isopropanol, adding a mixed solution of 1.2 g of vinyltrimethoxysilane, 6 mL of deionized water, and 44 mL of anhydrous ethanol, keeping the mixture at 75° C. for 4.5 h, centrifuging, washing, and drying to obtain the double-bonded nano-silica; The preparation of the composite zinc-titanium hydrotalcite comprises the following steps: (1) 3.7 g of zinc nitrate, 400 mL of ethanol, and 400 mL of deionized water were mixed, 1.1 mL of titanium tetrachloride was added, 0.4 g of dopamine hydrochloride was added and mixed, the pH was adjusted to 8, the mixture was transferred to a reactor, kept at 120°C for 23 h, centrifuged, and washed with ethanol and deionized water for 4 times in sequence to obtain polydopamine-coated zinc-titanium hydrotalcite; (2) 1.2 g of polydopamine-coated zinc-titanium hydrotalcite, 60 mL of anhydrous ethanol, and 60 mL of deionized water were mixed, ultrasonically stirred for 25 min, heated to 80 °C, 1.8 g of antibacterial hydrophobic copolymer was added, stirred for 2.5 h, centrifuged, washed, dried, and ground to obtain a composite zinc-titanium hydrotalcite; The preparation of the aqueous polyurethane emulsion comprises the following steps: Under a nitrogen atmosphere, 7 g of isophorone diisocyanate, 10 g of polycarbonate diol, and 3 drops of dibutyltin dilaurate were heated to 65°C in an oil bath for 2.5 h, a mixture of 0.8 g of 2,2-dihydroxymethylpropionic acid and 5 mL of acetone was added, the temperature was raised to 80°C and kept for 1.5 h, the temperature was lowered to 70°C, 2.8 g of castor oil and 5 mL of acetone were added, the temperature was lowered to 60°C, 1 g of pentaerythritol triacrylate and 1.4 g of antibacterial hydrophobic copolymer were added, the temperature was kept for 2.5 h, the temperature was lowered to 50°C, 0.8 g of triethylamine was added, deionized water was added for emulsification, and a water-based polyurethane emulsion with a solid content of 33% was obtained; The preparation of the antibacterial hydrophobic copolymer comprises the following steps: 1) Under nitrogen atmosphere, 9.1 mL of β-citronellol, 8.3 mL of triethylamine, and 100 mL of dichloromethane were mixed, transferred to an ice-water bath, 5.8 mL of methacryloyl chloride was added, and then kept at 20°C for 7.5 h, filtered under reduced pressure, concentrated by rotary evaporation, extracted with ether for 4 times, extracted and washed with dilute hydrochloric acid and saturated sodium bicarbonate solution twice, concentrated by rotary evaporation, and purified by silica gel column using n-hexane and ethyl acetate in a volume ratio of 9:1 as eluent to obtain citronellol methyl methacrylate; 2) 20 mL of deionized water and 0.5 g of sodium dodecyl sulfate were mixed, 3 g of styrene, 4.5 g of dodecafluoroheptyl methacrylate, 1.5 g of dimethylaminoethyl methacrylate, 1.1 g of citronellyl methyl methacrylate, and 1.2 g of 3-methacryloyl dopamine were added, and the mixture was stirred for 25 min, and 0.6 g of potassium persulfate and 20 mL of deionized water were added, and the mixture was heated to 80 ° C and kept warm for 2.5 h, cooled, centrifuged, washed, and dried to obtain an antibacterial hydrophobic copolymer; S4: coating the protective coating on the surface of the bamboo paint layer, photocuring the coating to form a protective layer, and obtaining a bamboo-like stainless steel guardrail; the working conditions of the photocuring treatment are: irradiating the surface of the bamboo paint layer with 365nm ultraviolet light for 5-10min.

[0024] Embodiment 3: A production and processing technology of bamboo-like stainless steel guardrail, comprising the following steps: S1: Assemble and weld the stainless steel pipes to obtain the stainless steel guardrail, and then perform grinding, polishing, washing and drying to obtain the pre-treated stainless steel guardrail; S2: applying the imitation bamboo paint on the surface of the pretreated stainless steel guardrail, drying it, and forming a bamboo paint layer; S3: mixing the waterborne polyurethane emulsion, the composite zinc-titanium hydrotalcite and the double-bonded nano-silica, adding a photoinitiator, and ultrasonically stirring to obtain a protective coating; The protective coating is composed of 57 parts of waterborne polyurethane emulsion, 2 parts of photoinitiator, 6 parts of composite zinc-titanium hydrotalcite, and 3 parts of double-bonded nano-silicon dioxide in parts by weight; The mass ratio of composite zinc-titanium hydrotalcite and double-bonded nano-silica is 2:1; The preparation of the double-bonded nano-silica comprises the following steps: mixing 2 g of nano-silica and 80 mL of isopropanol, adding a mixed solution of 1.2 g of vinyltrimethoxysilane, 6 mL of deionized water, and 44 mL of anhydrous ethanol, keeping the mixture at 80° C. for 4 h, centrifuging, washing, and drying to obtain the double-bonded nano-silica; The preparation of the composite zinc-titanium hydrotalcite comprises the following steps: (1) 3.7 g of zinc nitrate, 400 mL of ethanol, and 400 mL of deionized water were mixed, 1.1 mL of titanium tetrachloride was added, 0.4 g of dopamine hydrochloride was added and mixed, the pH was adjusted to 8, the mixture was transferred to a reactor, kept at 122 °C for 22 h, centrifuged, and washed with ethanol and deionized water for 5 times in sequence to obtain polydopamine-coated zinc-titanium hydrotalcite; (2) 1.2 g of polydopamine-coated zinc-titanium hydrotalcite, 60 mL of anhydrous ethanol, and 60 mL of deionized water were mixed, ultrasonically stirred for 30 min, heated to 82 °C, 1.8 g of antibacterial hydrophobic copolymer was added, stirred for 3 h, centrifuged, washed, dried, and ground to obtain a composite zinc-titanium hydrotalcite; The preparation of the aqueous polyurethane emulsion comprises the following steps: Under a nitrogen atmosphere, 7g of isophorone diisocyanate, 10g of polycarbonate diol, and 3 drops of dibutyltin dilaurate were heated to 68°C in an oil bath for 2h, a mixture of 0.8g of 2,2-dihydroxymethylpropionic acid and 5mL of acetone was added, the temperature was raised to 82°C and kept for 1h, the temperature was lowered to 72°C, 2.8g of castor oil and 5mL of acetone were added, the temperature was lowered to 62°C, 1g of pentaerythritol triacrylate and 1.4g of antibacterial hydrophobic copolymer were added, the temperature was kept for 3h, the temperature was lowered to 52°C, 0.8g of triethylamine was added, deionized water was added for emulsification, and a water-based polyurethane emulsion with a solid content of 33% was obtained; The preparation of the antibacterial hydrophobic copolymer comprises the following steps: 1) Under nitrogen atmosphere, 9.1 mL of β-citronellol, 8.3 mL of triethylamine, and 100 mL of dichloromethane were mixed, transferred to an ice-water bath, 5.8 mL of methacryloyl chloride was added, and then kept at 25°C for 8 h, filtered under reduced pressure, concentrated by rotary evaporation, extracted with ether for 5 times, extracted and washed with dilute hydrochloric acid and saturated sodium bicarbonate solution for 3 times, concentrated by rotary evaporation, and purified by silica gel column using n-hexane and ethyl acetate in a volume ratio of 9:1 as eluent to obtain citronellol methyl methacrylate; 2) 20 mL of deionized water and 0.5 g of sodium dodecyl sulfate were mixed, 3 g of styrene, 4.5 g of dodecafluoroheptyl methacrylate, 1.5 g of dimethylaminoethyl methacrylate, 1.1 g of citronellyl methyl methacrylate, and 1.2 g of 3-methacryloyl dopamine were added, and the mixture was stirred for 20-30 min, and 0.6 g of potassium persulfate and 20 mL of deionized water were added, and the mixture was heated to 82 ° C and kept warm for 2 h, cooled, centrifuged, washed, and dried to obtain an antibacterial hydrophobic copolymer; S4: coating the protective coating on the surface of the bamboo paint layer, photocuring the coating to form a protective layer, and obtaining a bamboo-like stainless steel guardrail; the working conditions of the photocuring treatment are: irradiating the bamboo paint layer under 365nm ultraviolet light for 8 minutes.

[0025] Comparative Example 1: Taking Example 3 as the control group, the composite zinc-titanium hydrotalcite was replaced with the zinc-titanium hydrotalcite coated with polydopamine, and the other processes were normal.

[0026] Comparative Example 2: Taking Example 3 as the control group, the aqueous polyurethane emulsion was replaced with aqueous polyurethane (BZ-7: Changzhou Baichang Coatings Technology Co., Ltd.), and the other processes were normal.

[0027] Comparative Example 3: Example 3 was used as the control group, in which no antibacterial hydrophobic copolymer was prepared, and other processes were normal.

[0028] The thickness of the bamboo lacquer layer and the protective layer are both 20µm.

[0029] Sources of raw materials used (for demonstration purposes only): Imitation bamboo paint: Wuhu Paint Chemical Co., Ltd., Ningjin County, Shandong Province; Stainless steel pipe: In terms of mass percentage, its chemical composition is: carbon 0.008%, silicon 0.323%, manganese 1.12%, chromium 17.11%, nickel 10.45%, molybdenum 2.07%, and the balance is iron; Photoinitiator 2959S60365: Shanghai Yuanye Biotechnology Co., Ltd.; 3-methacryloyl dopamine A0915896: Henan Weitixi Chemical Technology Co., Ltd.; Polycarbonate diol QF0424: Hubei Qifei Pharmaceutical Chemical Co., Ltd.; Nano-silicon dioxide S490064, vinyl trimethoxysilane V162969, zinc nitrate Z190758, dopamine hydrochloride D103111, isophorone Diisocyanate I109582, dibutyltin dilaurate D100274, castor oil C110663, 2,2-dihydroxymethylpropionic acid B104539, pentaerythritol triacrylate P189117, β-citronellol C102066, triethylamine T103285, methacryloyl chloride M109517, styrene S110375, dodecafluoroheptyl methacrylate D301595, dimethylaminoethyl methacrylate D111129, sodium dodecyl sulfate S108347: Aladdin reagent; isopropanol, anhydrous ethanol, titanium tetrachloride, acetone, dichloromethane, ether, hydrochloric acid, sodium bicarbonate, n-hexane, ethyl acetate, potassium persulfate, analytical grade: Sinopharm reagent.

[0030] Performance test: The stainless steel guardrails prepared in the embodiments and comparative examples were tested: Antibacterial property: Escherichia coli was used as the test strain and the plate method was used for testing; Hydrophobicity: The water contact angle was used for characterization, and the tester tested 4μL of deionized water droplets; Ultraviolet resistance: The bamboo-proof stainless steel guardrail was irradiated with 365nm ultraviolet light for 3d, and then the antibacterial property test was carried out, and compared with the sample without ultraviolet irradiation, the antibacterial change rate was 0-1% (including 1%), which was excellent, otherwise it was unqualified; the results are shown in Table 1; Table 1

[0031] The present invention provides a production and processing technology for a bamboo-like stainless steel guardrail. By optimizing the coating composition and the processing technology, a super-hydrophobic, antibacterial, anti-ultraviolet and corrosion-resistant bamboo-like stainless steel guardrail is prepared, thereby greatly extending the service life of the bamboo-like stainless steel guardrail.

[0032] By comparing Example 3 with Comparative Examples 1 and 3, it can be seen that in order to give the bamboo-like stainless steel guardrail excellent UV resistance, the present invention introduces composite zinc-titanium hydrotalcite as a filler in the protective coating, uses anhydrous zinc acetate, titanium tetrachloride, and dopamine hydrochloride as raw materials, and uses a hydrothermal method to prepare polydopamine-coated zinc-titanium hydrotalcite. In order to improve the uniformity of dispersion of the polydopamine-coated zinc-titanium hydrotalcite in the protective coating, dopamine in the polydopamine-coated zinc-titanium hydrotalcite is used as an anchoring agent, and 3-methacryloyl dopamine and styrene, dodecafluoroheptyl methacrylate, The invention discloses an antibacterial hydrophobic copolymer synthesized by using dimethylaminoethyl methacrylate and citronellyl methyl methacrylate as raw materials. In the copolymer, dodecafluoroheptyl methacrylate gives it low surface energy, and the cationic monomers dimethylaminoethyl methacrylate and citronellyl methyl methacrylate synergistically give it excellent antibacterial properties. Citronellyl methyl methacrylate is prepared by modifying the natural antibacterial agent citronellol through an esterification reaction. 3-Methacryloyl dopamine is beneficial for the copolymer to be deposited on the surface of the zinc-titanium hydrotalcite coated with polydopamine, thereby giving the composite zinc-titanium hydrotalcite excellent antibacterial and hydrophobic properties.

[0033] By comparing Example 3 with Comparative Example 2 and Comparative Example 3, it can be seen that in the present invention, water-based polyurethane emulsion is used as the base material of the photocurable protective coating, isophorone diisocyanate and polycarbonate diol are used as raw materials to prepare the prepolymer, dimethylol propionic acid is used as a hydrophilic chain extender, castor oil is used as an internal cross-linking agent, and pentaerythritol triacrylate and an antibacterial hydrophobic copolymer are used for end-capping modification, which greatly improves the bonding strength between the coating and the stainless steel guardrail, improves the hydrophobicity and antibacterial property of the coating, and prolongs the service life of the stainless steel guardrail.

[0034] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A production and processing technology of imitation bamboo stainless steel guardrail, characterized in that: The following steps are involved: S1: Assemble and weld the stainless steel pipes to obtain the stainless steel guardrail, and then perform grinding, polishing, washing and drying to obtain the pre-treated stainless steel guardrail; S2: applying the imitation bamboo paint on the surface of the pretreated stainless steel guardrail, drying it, and forming a bamboo paint layer; S3: mixing the waterborne polyurethane emulsion, the composite zinc-titanium hydrotalcite and the double-bonded nano-silica, adding a photoinitiator, and ultrasonically stirring to obtain a protective coating; S4: coating the protective coating on the surface of the bamboo paint layer, and performing light curing to form a protective layer, thereby obtaining a bamboo-like stainless steel guardrail.

2. The production and processing technology of the bamboo-like stainless steel guardrail according to claim 1 is characterized in that: The protective coating comprises, by weight, 31-57 parts of aqueous polyurethane emulsion, 1-2 parts of photoinitiator, 2-6 parts of composite zinc-titanium hydrotalcite, and 1-3 parts of double-bonded nano-silicon dioxide.

3. The production and processing technology of the bamboo-like stainless steel guardrail according to claim 1 is characterized in that: The mass ratio of the composite zinc-titanium hydrotalcite to the double-bonded nano-silica is 2:

1.

4. The production and processing technology of the bamboo-like stainless steel guardrail according to claim 1 is characterized in that: The working conditions of the light curing treatment are: irradiation under 365nm ultraviolet light for 5-10min.

5. The production and processing technology of the bamboo-like stainless steel guardrail according to claim 1 is characterized in that: The preparation of the double-bonded nano-silica comprises the following steps: mixing nano-silica and isopropanol, adding a mixed solution of vinyltrimethoxysilane, deionized water and anhydrous ethanol, keeping warm at 70-80°C for 4-5h, centrifuging, washing and drying to obtain the double-bonded nano-silica.

6. The production and processing technology of the bamboo-like stainless steel guardrail according to claim 1 is characterized in that: The preparation of the composite zinc-titanium hydrotalcite comprises the following steps: (1) Mix zinc nitrate, ethanol and deionized water, add titanium tetrachloride, add dopamine hydrochloride and mix, adjust the pH to 8, transfer to a reactor, keep warm at 118-122°C for 22-24 hours, centrifuge, wash with ethanol and deionized water for 3-5 times, and obtain polydopamine-coated zinc-titanium hydrotalcite; (2) The polydopamine-coated zinc-titanium hydrotalcite, anhydrous ethanol and deionized water are mixed, ultrasonically stirred for 20-30 minutes, heated to 78-82°C, added with an antibacterial hydrophobic copolymer, stirred for 2-3 hours, centrifuged, washed, dried and ground to obtain a composite zinc-titanium hydrotalcite.

7. The production and processing technology of the bamboo-like stainless steel guardrail according to claim 1 is characterized in that: The preparation of the aqueous polyurethane emulsion comprises the following steps: In a nitrogen atmosphere, isophorone diisocyanate, polycarbonate diol and dibutyltin dilaurate are mixed, the temperature is raised to 63-68°C in an oil bath for 2-3 hours, a mixture of 2,2-dihydroxymethylpropionic acid and acetone is added, the temperature is raised to 78-82°C and kept warm for 1-2 hours, the temperature is lowered to 68-72°C, a mixture of castor oil and acetone is added, the temperature is lowered to 58-62°C, pentaerythritol triacrylate and antibacterial hydrophobic copolymer are added, the temperature is kept warm for 2-3 hours, the temperature is lowered to 48-52°C, triethylamine is added, deionized water is added for emulsification, and a waterborne polyurethane emulsion is obtained by rotary evaporation.

8. The production and processing technology of imitation bamboo stainless steel guardrail according to claim 7 is characterized in that: The mass ratio of the isophorone diisocyanate, the polycarbonate diol, the 2,2-dihydroxymethyl propionic acid, the castor oil, the pentaerythritol triacrylate and the antibacterial hydrophobic copolymer is 7:10:0.8:1.5:1:1.

4.

9. The production and processing technology of the bamboo-like stainless steel guardrail according to claim 6 or 7, characterized in that: The preparation of the antibacterial hydrophobic copolymer comprises the following steps: 1) Under a nitrogen atmosphere, β-citronellol, triethylamine and dichloromethane were mixed, transferred to an ice-water bath, methacryloyl chloride was added, and then kept at 18-25°C for 7-8h, filtered under reduced pressure, concentrated by rotary evaporation, extracted with ether for 3-5 times, extracted and washed with dilute hydrochloric acid and saturated sodium bicarbonate solution for 1-3 times, concentrated by rotary evaporation, and purified by silica gel column using n-hexane and ethyl acetate in a volume ratio of 9:1 as eluent to obtain citronellol methyl methacrylate; 2) Mix deionized water and sodium dodecyl sulfate, add styrene, dodecafluoroheptyl methacrylate, dimethylaminoethyl methacrylate, citronellyl methyl methacrylate, and 3-methacryloyl dopamine, stir for 20-30 minutes, add a mixture of potassium persulfate and deionized water, heat to 78-82° C. and keep warm for 2-3 hours, cool, centrifuge, wash, and dry to obtain an antibacterial hydrophobic copolymer.

10. A bamboo-like stainless steel guardrail, characterized in that: The product is obtained by the process described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Highly wear-resisting antibacterial water-based ultraviolet curing paint

    CN104277675A

  • Construction technology for building outer wall decoration with bamboo imitating effect

    CN107327099A

  • Preparation method and application of modified anti-corrosion super-hydrophobic integrated coating

    CN112300697A

  • Preparation method of waterborne polyurethane waterproof coating

    CN115433482A

  • Bioadhesive hydrotalcite-polydopamine skin composite light screening agent and preparation method thereof

    CN116327640A

Cited By

  • Treating agent for surface corrosion prevention of zinc-aluminum-magnesium alloy and preparation method of treating agent

    CN121851849A